NF kappaB expression increases and CFTR and MUC1 expression decreases in the endometrium of infertile patients with hydrosalpinx: a comparative study - Song Yong; Wang Qiushi; Huang Wei; Xiao Li; Shen Licong; Xu Wenming (BMC, 2012)
Abstract Background Hydrosalpinx are associated with infertility, due to reduced rates of implantation and increased abortion rates. The aims of this study were to investigate the expression of cystic fibrosis transmembrane conductance regulator (CFTR), nuclear factor kappa B (NF KappaB) and mucin-1 (MUC-1), and analyze the correlation between the expression of CFTR and NF KappaB or MUC1, in the endometrium of infertile women with and without hydrosalpinx. Methods Thirty-one infertile women with laparoscopy-confirmed unilateral or bilateral hydrosalpinx and 20 infertile women without hydrosalpinx or pelvic inflammatory disease (control group) were recruited. Endometrial biopsy samples were collected and the expression of CFTR, NF KappaB and MUC1 were analyzed using immunohistochemistry and quantitative real-time PCR. Results CFTR, NF KappaB and MUC1 mRNA and protein expression tended to increase in the secretory phase compared to the proliferative phase in both groups; however, these differences were not significantly different. The endometrium of infertile patients with hydrosalpinx had significantly higher NF KappaB mRNA and protein expression, and significantly lower CFTR and MUC1 mRNA and protein expression, compared to control infertile patients. A positive correlation was observed between CFTR and MUC1 mRNA expression (r = 0.65, P < 0.05); a negative correlation was observed between CFTR mRNA and NF KappaB mRNA expression (r = −0.59, P < 0.05). Conclusions Increased NF KappaB expression and decreased CFTR and MUC1 expression in the endometrium of infertile patients with hydrosalpinx reinforce the involvement of a molecular mechanism in the regulation of endometrial receptivity.